Peter Doherty on genomics, trypanosomosis disease resistance, and increased yields - Doherty, Peter F. (International Livestock Research Institute, 2016)
Peter Doherty, Nobel Prize Laureate for Physiology or Medicine–1996, and ILRI patron, on genomics, trypanosomiasis disease resistance, and increasing yields. Filmed in September 2016.